2010
DOI: 10.4161/cc.9.9.11525
|View full text |Cite
|
Sign up to set email alerts
|

Cohesin is needed for bipolar mitosis in human cells

Abstract: Multi-polar mitosis is strongly linked with aggressive cancers and it is a histological diagnostic of tumor-grade. However, factors that cause chromosomes to segregate to more than two spindle poles are not well understood. Here we show that cohesins Rad21, Smc1 and Smc3 are required for bipolar mitosis in human cells. After Rad21 depletion, chromosomes align at the metaphase plate and bipolar spindles assemble in most cases, but in anaphase the separated chromatids segregate to multiple poles. Time-lapse micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 39 publications
(57 reference statements)
2
40
0
Order By: Relevance
“…In support of this idea, all elements of the cohesin complex are found in the centrosome, and cohesin depletion results in centriole disengagement. [37][38][39][40] Furthermore, knockdown of an isoform of the cohesin-binding protein, SGO1 (shugoshin), causes centriole splitting. 41 Intriguingly, experimental evidence also suggests that cleaved cohesin promotes continued centriole engagement, 34,38,42 perhaps by delivering 'engagement factors' to the centrosome to preserve centriole cohesion until G1.…”
Section: Excess Baggage: How Cancer Cells Acquire Extra Centrosomesmentioning
confidence: 99%
See 1 more Smart Citation
“…In support of this idea, all elements of the cohesin complex are found in the centrosome, and cohesin depletion results in centriole disengagement. [37][38][39][40] Furthermore, knockdown of an isoform of the cohesin-binding protein, SGO1 (shugoshin), causes centriole splitting. 41 Intriguingly, experimental evidence also suggests that cleaved cohesin promotes continued centriole engagement, 34,38,42 perhaps by delivering 'engagement factors' to the centrosome to preserve centriole cohesion until G1.…”
Section: Excess Baggage: How Cancer Cells Acquire Extra Centrosomesmentioning
confidence: 99%
“…[37][38][39][40] Furthermore, knockdown of an isoform of the cohesin-binding protein, SGO1 (shugoshin), causes centriole splitting. 41 Intriguingly, experimental evidence also suggests that cleaved cohesin promotes continued centriole engagement, 34,38,42 perhaps by delivering 'engagement factors' to the centrosome to preserve centriole cohesion until G1. 38 Clearly, more data are awaited to clarify how centrioles remain engaged for the appropriate segment of the cell cycle and subsequently part ways in an exquisitely timed manner.…”
Section: Excess Baggage: How Cancer Cells Acquire Extra Centrosomesmentioning
confidence: 99%
“…In this special issue of Cell Cycle, three papers from the Clarke group further confirmed that the mammalian cohesin subunit, Scc1/Rad21, indeed localized at the spindle poles/centrosomes through very detailed live imaging and RNAi depletion assays. [43][44][45] Beauchene et al found that Rad21 is required for centrosome integrity in human cells independently of its role in chromosome cohesion. 43 Giménez-Abián et al showed that the cohesin protein Rad21 localizes to centrosomes in a manner that is dependent upon known regulators of sister chromatid cohesion as well as regulators of centrosome function.…”
Section: -24mentioning
confidence: 99%
“…These new data are consistent with a non-chromosomal function of cohesin. 44 In addition, Nakamura et al discovered that centrosomes harbor the protein Aki1 (Akt kinase-interacting protein 1), which promotes centriole integrity. Interestingly, Aki1 interaction with cohesin subunit Scc1 prevents centrioles from splitting too soon; Aki1 also binds another cohesin component, SA-2.…”
Section: -24mentioning
confidence: 99%
See 1 more Smart Citation